Liberales exaltados republicanizados en la prensa de Barcelona del Trienio Liberal - Jordi Roca Vernet (El Argonauta Español)
Based on the analysis of the exalted liberal press of Barcelona, this article demonstrates how a revolutionary republican political alternative emerged in Spain. The Patriotic Tertulia de Lacy became the central space of exalted liberalism in Barcelona, where a republican minority was expressed in revolutionary key and linked to carbonería. This republicanism was evident through three debates: the inviolability of the monarch, the need to subvert the legal order to ensure the survival of the liberal regime, and the development of a republican morality that questioned Christian. The emergence of this republicanism was decisive for the implementation of a form of revolutionary government in the local space during the siege that suffered the city of Barcelona in the spring and summer of 1823.